Case Report: A novel desmoplakin mutation in a taiwanese woman with familial dilated cardiomyopathy that necessitated heart transplantation - Chang, Yi-Han; Lin, Pei; Lin, Jia-Ling; Huang, Hsin-Yu; Hsu, Chao-Kai; Hsu, Chih-Hsin (Frontiers in Genetics, 2022)
Around one third of patients diagnosed with idiopathic dilated cardiomyopathy (DCM) turn out to be familial cases, with the subsequent identification of a pathogenic variant. Cardiomyopathy caused by desmoplakin gene mutations represents a distinct form with a high prevalence of left ventricle involvement. We report a novel desmoplakin mutation in a Taiwanese family, in which the proband recovered well after heart transplantation and under medical control. The present study broadens the genetic spectrum of this disease entity and strengthens the notion that a detailed family history with genetic study contributes to the early detection and treatment of inherited diseases.